O Porto do Metro - Filipe Tomé Delgado da Torre (2019)
This thesis has as its main objective a comprehensive analysis of how the interventionof Metro do Porto was inserted and integrated in urban contexts with intense dynamics,when their vehicles run on the surface. Thus, the cities of Matosinhos, through the LinhaAzul (Blue Line), and Vila do Conde and Póvoa de Varzim, with the Linha Vermelha (RedLine), were selected.With this trajectory in mind, the dissertation is divided into three diferent moments.The first part seeks to understand the evolution of urbanism over time, morespecifically, how large infrastructure projects have affected the physical and social spheresof the cities in which they operate. Starting from the 19th century with the Bazalgettesewers in London, it will advance through the different phases experienced by urbanismuntil the beginning of the millennium.In a second phase, the light railway transit is placed under the magnifying glass.After understanding its origins and fundamental qualities, we seek to understand howthis system relates and interacts with different urban characteristics. This relationship willthen be deconstructed and an attempt will be made to create a comparative link with thesituation in Porto.The third and last phase is dedicated to Metro do Porto. After a trip back in time,where the system's path is revived from a myth to the network as we know it today, weembarked on two other trips, the Blue and Red lines. Now with the knowledge of howinfrastructure, physical and social relate, and how a public transport system interactswith the city, we will analyze the large and small scale of Metro do Porto's intervention inMatosinhos and Póvoa de Varzim.